Langman's medical embryology - Sadler, T. W. (Wolters Kluwer, 2024)
Concise, clearly written, and vibrantly illustrated, Langman's Medical Embryology, 15th Edition, makes complex embryology concepts approachable to help you build the clinical understanding essential to your success in medical practice, nursing, or other health professions. Hundreds of full-color illustrations clarify the stages of embryonic development with rich detail, and engaging learning features, clinical examples, and online review questions ready you for the challenges ahead on your exams and in clinical practice.